Oocyte final maturation, egg development and effects of stripping timings on egg quality in Pangasius hypophthalmus and Clarias gariepinus - Arun Prasad Baidya (2004)
River catfish, Pangasius hypophthalmus and African catfish, Clarias gariepinus have become popular in the aquaculture industry due to several reasons: high growth rate, omnivorous feeding habits, strong resistance to disease and tolerance to low dissolved oxygen level. These two species are now major cultured catfishes in the Southeast Asia. Although their seeds have been produced by hormone-induced reproduction, mass seed production has remained a major constraint due to low fertilization and hatching rates. Important information on basic biological features of oocytes and eggs development of these species is still lacking and could limit aquaculture development. The present industrial application research study was conducted to understand the optimum ovulation time and duration for stripping of good quality eggs of these two morphologically different species with the objective of improving mass seed production. Oocyte final maturation and ovulation were induced by two human chorionic gonadotropin injections (500 and 1500 IU/kg at a 14-h interval) in P. hypophthalmus, and a single dose of Ovaprim (0. 5 ml/kg) in C. gariepinus. Oocytes were continuously monitored by cannulation. The stages of egg development were obs(:Jrved under a microscope. The eggs were stripped and fertilized at hourly intervals after ovulation. The fertilization and hatching rates were obse,ved from the eggs stripped at different times to determine the egg quality. The different grades of oocyte final maturation were divided into six grades. The oocyte final maturation was at grade I in P. hypophthalmus and Ill in C. gariepinus prior to hormone treatment and the fish released eggs at grade VI. The egg stripping time was water temperature dependent, which decreased with increasing water temperature. The fertilization and hatching rates of eggs stripped at different times were decreased with the time after ovulation. In six females of P. hypophthalmus (1.8-3.3 kg), the mean fertilization rates were 92.4% at 0 h after ovulation (AO) and 15. 7% at 8 h AO; and the mean hatching rate was 80.6% at Oh AO and finally decreased to 0% at 6 h AO. In six females of C. gariepinus (0.6-1.3 kg), the mean fertilization rates were 92.2% at 0 h AO and 40.6% at 6 h AO; and the mean hatching rate was 83. 7% at Oh AO and finally decreased to 0% at 6-8 h AO. This study concludes that high fertilization and hatching rates can be achieved by determining the optimum timing for egg stripping by monitoring oocyte final maturation, which was estimated at 7 h 30 min-14 h 30 min after the second hormone treatment at 26. 0-33. 5°C in P. hypophthalmus and 7-8 h after the hormone treatment at 27. 0- 28. 0°C in C. gariepinus. Above study also concludes that good quality eggs (more than 50% hatching rate on average) can be achieved by stripping and fertilization of the eggs within 2 h AO in P. hypophthalmus and 3 h AO in C. gariepinus.